KOORDINASI DINAS PEMBERDAYAAN MASYARAKAT DAN DESA KABUPATEN KAMPAR DALAM PENYELESAIAN MASALAH PENYELENGGARAAN PEMERINTAHAN DESA - Indah Wahyuni; Adianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The administration of village governance is inseparable from the organization of good coordination between village officials. Village goverment is the leading in service to the community and a strategic spearhead for the success of all programs. Therefore, efforts to strengthen villages are a step to accelerate the realization of people’s welfare as regional autonomy. So that the administration of village governance is a sub system of governance, so that the village has the authority to regulate and manage the interest of it people. The purpose of this research is to find out how the coordination carried out by the village and village empowerment agency Kampar regency in solving the problem of village governance and what factors are the obstacles. As for the theory used in this study is coordination by Koonz, O’Donnel and Fayol, namely cooperation, division of tasks, communication, meeting meetings. This study uses qualitative research, with a phenomenological approach obtained through interviews, observations and documentation. The result of this study indicate that, firstly the coordination in solving the problem of the implementation of village government as whole has not run optimally. Both in cooperatif, division of tasks, communication and in meetings there are still obstacles encountered. The two factors which become obstacles in coordinating the resolution of the problem of village governace are limited human resources and budget constraints.Keywords: Coordination, Organiation and village government